Applying the Modified Five-Item Frailty Index to Predict Complications following Lower Extremity Free Flap Reconstruction in Trauma Patients - Gonzalez, Miguel; Zietowski, Maeson; Patel, Ronak; Chattha, Anmol; Cripps, Courtney N.; Beederman, Maureen (Journal of Reconstructive Microsurgery, 2025)
Free flap reconstruction in the setting of lower extremity trauma continues to be a challenging clinical problem fraught with a high risk of complications including flap compromise. Although studies have described certain risk factors that predispose these patients to poor outcomes, there remains a paucity of literature detailing frailty as a risk factor. As such, the aim of our study was to examine the application of the 5-item modified frailty index (mFI-5) in trauma patients undergoing lower extremity free flap reconstruction.The 2012 to 2020 American College of Surgeons-National Surgical Quality Improvement Program database was queried for lower extremity free flap reconstructive procedures. After excluding nontrauma etiologies, patients were stratified into three cohorts by their respective mFI-5 score (0, 1, and ≥2). Univariate and multivariate logistic regressions were performed to assess the effect of mFI-5 scores on postoperative complications.A total of 219 patients were included (64.8% male) with an average age of 47.6 ± 16 years. A total of 22.4% (n = 49) of patients had at least one complication. An increased mFI-5 score was associated with an increase in any complication (p < 0.001), hematological complication (p = 0.023), and reoperation (p = 0.004) rates. A high mFI-5 score was found to be an isolated risk factor for having at least one complication (mFI-5 ≥ 2: odds ratio [OR]: 3.829; p < 0.007; 95% confidence interval [CI]: 1.445–10.145) and reoperation (mFI-5 ≥ 2: OR: 5.385; p < 0.002; 95% CI: 1.826–15.877).Our results indicate that the mFI-5 can be a helpful assessment tool for lower extremity trauma patients undergoing free flap reconstruction to predict the risk of surgical complications and reoperation rates. Patients with an mFI-5 score > 2 should be counseled preoperatively of their increased risk of complications.
Keywords: frailty; limb salvage; trauma; free flap; lower extremity; mFI-5